2011
DOI: 10.1016/j.gde.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation by receptor tyrosine kinases: analysis of the Gurken gradient in Drosophila oogenesis

Abstract: Spatial patterns of cell differentiation in developing tissues can be controlled by receptor tyrosine kinase (RTK) signaling gradients, which may form when locally secreted ligands activate uniformly expressed receptors. Graded activation of RTKs can span multiple cell diameters, giving rise to spatiotemporal patterns of signaling through the Extracellular Signal Regulated/Mitogen Activated Protein Kinase (ERK/MAPK), which connects receptor activation to multiple aspects of tissue morphogenesis. This general m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…The control of dorsal appendage formation in D. melanogaster eggshells has been extensively studied, with a major focus on patterning by morphogen gradients and the downstream cascades of signaling and transcription (Berg, 2005;Cheung et al, 2011;Wu et al, 2008). Several studies have also examined patterning of the follicular epithelium in other drosophilid species (James and Berg, 2003;Kagesawa et al, 2008;Marmion et al, 2013;Nakamura et al, 2007;Nakamura and Matsuno, 2003;Niepielko et al, 2011Niepielko et al, , 2012Peri et al, 1999;Vreede et al, 2013;Zartman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The control of dorsal appendage formation in D. melanogaster eggshells has been extensively studied, with a major focus on patterning by morphogen gradients and the downstream cascades of signaling and transcription (Berg, 2005;Cheung et al, 2011;Wu et al, 2008). Several studies have also examined patterning of the follicular epithelium in other drosophilid species (James and Berg, 2003;Kagesawa et al, 2008;Marmion et al, 2013;Nakamura et al, 2007;Nakamura and Matsuno, 2003;Niepielko et al, 2011Niepielko et al, , 2012Peri et al, 1999;Vreede et al, 2013;Zartman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila oogenesis is one of the most extensively studied models of EGFR signaling in development. In this case, a gradient of EGFR activation is established by Gurken (GRK), a ligand that is secreted from the oocyte and signals through receptors in the follicular epithelium (5). Acting in concert with other pathways, EGFR controls region-specific expression of multiple genes involved in patterning of the Drosophila eggshell, a complex structure that holds inductive cues necessary for body axes specification during embryogenesis (6).…”
mentioning
confidence: 99%
“…miR-318 is uniformly expressed in somatically derived follicle cells during late oogenesis. It has been shown that spatial gene expression patterns in the follicle cells follow a simple combinatorial code based on six basic shapes, including the uniform pattern (Yakoby et al 2008;Cheung et al 2011). The uniform expression pattern of miR-318 in the follicle cells may reflect its function as a uniform repressor.…”
Section: Discussionmentioning
confidence: 99%